Impact of grey literature on systematic reviews of randomized trials - Hopewell, S (2004)
Systematic reviews are increasingly important in evidence-based medicine. Their validity is dependent on the underlying data, thus any decisions about the eligibility of trials based on where they are published, for example excluding trials from the grey literature, could _bias their results and conclusions. However, the identification and inclusion of trials published in the grey literature can be time consuming and difficult. This thesis assesses the actual and potential impact of including trials reported in the grey literature in systematic reviews of healthcare interventions. A review of existing knowledge in this area was first carried out. Four substantial projects were then conducted.